Numerical Simulation and Analysis of Cycloidal Gear Forming Grinding Temperature Field - Ke Qingxun; Deng Xiaozhong; Su Jianxin; Nie Shaowu; Hu Chenhui (Jixie chuandong)
Forming grinding process is one of the methods for finishing the cycloidal gear. When the grinding process parameters are not suitable,the instantaneous heat generated in the grinding zone will cause the tooth surface burn. In order to optimize the grinding process parameters and prevent tooth surface burn,it is necessary to simulate the temperature field distribution of tooth surface. Using theoretical analysis to calculate the grinding energy and heat distribution ratio in the process of grinding,using finite element method and the computer simulation software of cycloid gear form grinding temperature field distribution in the process of simulation,the tooth surface temperature with the change of grinding time and temperature field distribution in gear tooth surface are got. Through the simulation analysis,it is found that the velocity vw of the grinding wheel and the radial feed grinding depth ap have a great influence on the distribution of the temperature field of the tooth surface,during the entire grinding process,the maximum temperature of the transient temperature field of the tooth surface appears near the tip of the tooth surface of the cycloid gear. And the maximum error of the simulation results and theoretical analysis is within 10%,which is of great value for the prediction of the distribution of the temperature field of the tooth surface and the reasonable selection of the grinding process parameters.